Venture capital on a shoestring: Bioventures' pioneering life sciences fund in South Africa - Singer Peter A; Masum Hassan (BMC, 2010)
Abstract Background Since 2000, R&D financing for global health has increased significantly, with innovative proposals for further increases. However, although venture capital (VC) funding has fostered life sciences businesses across the developed world, its application in the developing world and particularly in Africa is relatively new. Is VC feasible in the African context, to foster the development and application of local health innovation? As the most industrially advanced African nation, South Africa serves as a test case for life sciences venture funding. This paper analyzes Bioventures, the first VC company focused on life sciences investment in sub-Saharan Africa. The case study method was used to analyze the formation, operation, and investment support of Bioventures, and to suggest lessons for future health venture funds in Africa that aim to develop health-oriented innovations. Discussion The modest financial success of Bioventures in challenging circumstances has demonstrated a proof of concept that life sciences VC can work in the region. Beyond providing funds, support given to investees included board participation, contacts, and strategic services. Bioventures had to be proactive in finding and supporting good health R&D. Due to the fund's small size, overhead and management expenses were tightly constrained. Bioventures was at times unable to make follow-on investments, being forced instead to give up equity to raise additional capital, and to sell health investments earlier than might have been optimal. With the benefit of hindsight, the CFO of Bioventures felt that partnering with a larger fund might benefit similar future funds. Being better linked to market intelligence and other entrepreneurial investors was also seen as an unmet need. Summary BioVentures has learned lessons about how the traditional VC model might evolve to tackle health challenges facing Africa, including how to raise funds and educate investors; how to select, value, and support investments; and how to understand the balance between financial and social returns. The experience of the fund suggests that future health funds targeting ailments of the poor might require investors that accept health benefits as part of their overall "return." Learning from Bioventures may help develop health innovation funding for sub-Saharan African that has combined health, financial, and economic development impacts.